Reframing Student Engagement through the Lens of the English Language Learner Experience - Cook, Keely (2018)
Student engagement (SE) is a topic of particular importance within higher education circles given the growing body of evidence linking engagement to achievement. However, the ways in which SE is conceptualised and measured has led to much theorising and debate, raising criticisms that there is too much emphasis on the generic learner. This study narrows the SE focus by examining the SE experiences of a group of twenty-two English language learners in a university pathway program. The study begins with a working framework, derived from Kahu’s (2013) synthesis of various student engagement perspectives, that views the influences to engagement as separate from the state of being engaged, ultimately leading to engagement outcomes. From this conceptualisation of SE, both qualitative and quantitative methods of data collection were used to investigate how SE and student success manifested within the learning experiences of the research participants. Findings revealed that the majority valued and were positively influenced by the relational aspects of their learning environments, including structured peer and teacher interactions, as well those aspects of the course that contributed to their academic and discipline-specific language skill development. Students demonstrated their engagement in the classroom through their use of English and most experienced not only academic achievement, but also successes characterized by increased confidence and social capital, as well as noticeable language improvement. However, fewer students reported feeling a sense of connection to their discipline and wider campus community at the end of the program. Based on the findings, context-based recommendations are made to enhance SE inputs within the program. The study concludes with the suggestion that language proficiency,learning and use should be considered as key indicators within SE frameworks and instruments of measurement in order to expand discussions of SE to include engagement with language and the ability of language to facilitate success.